1999
DOI: 10.1093/rheumatology/38.8.724
|View full text |Cite
|
Sign up to set email alerts
|

High disease activity at baseline does not prevent a remission in patients with systemic lupus erythematosus

Abstract: SLE patients with severe initial clinical manifestations and higher SLEDAI values may achieve clinical remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 14 publications
2
20
1
Order By: Relevance
“…Previous studies have used a SLEDAI score to evaluate disease activity (9,12). However, in our study, disease activity was measured by BILAG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have used a SLEDAI score to evaluate disease activity (9,12). However, in our study, disease activity was measured by BILAG.…”
Section: Discussionmentioning
confidence: 99%
“…Formiga et al (9) reported that 24 of 100 white patients achieved remission at least for a year and remained in remission for an average time of 55 months. They used the SLEDAI score to assess activity since the onset of disease, and found that higher SLEDAI scores correlated with later remission.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies addressing the issue of remission in SLE reported divergent results 7–9 12 16 18 24. The main reasons for discrepancies among these studies are the use of different definitions of remission.…”
Section: Discussionmentioning
confidence: 99%
“…Other common minimal durations are 1 and 2 years. Different studies have shown quite consistent results for the 1 year remission rates, with ranges between 18.9% and 28.4% if serological activity was allowed 1 2 12 13 15. In one study where serological activity was not allowed, the 1 year remission rate was just 6.5% 12.…”
Section: Introductionmentioning
confidence: 88%